2018
DOI: 10.3851/imp3193
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue Volume and Cardiovascular Risk Indices among Asymptomatic Women with and without HIV

Abstract: Asymptomatic women with and without HIV have similar volumes of EAT, but drivers of EAT may differ between groups. HIV-infected women with excess EAT have highest-level immune activation and the highest percentage of non-calcified plaque. Future studies are needed to determine whether EAT contributes pathogenetically to HIV-associated cardiovascular disease in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In our study, we found a positive association between epicardial fat volume and exposure to ART, and more specifically to NNRTIs. Although there have been reports of increased epicardial fat with exposure to NRTIs [25,34,40], and protease inhibitors [41], this finding related to NNRTIs is novel. It should be noted, however, that combinations of ARTs were used in our participants, and therefore, we cannot exclude that the increase of epicardial fat associated to NNRTI may result from a combination effect of NNRTI with other classes, in particular the NRTIs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, we found a positive association between epicardial fat volume and exposure to ART, and more specifically to NNRTIs. Although there have been reports of increased epicardial fat with exposure to NRTIs [25,34,40], and protease inhibitors [41], this finding related to NNRTIs is novel. It should be noted, however, that combinations of ARTs were used in our participants, and therefore, we cannot exclude that the increase of epicardial fat associated to NNRTI may result from a combination effect of NNRTI with other classes, in particular the NRTIs.…”
Section: Discussionmentioning
confidence: 95%
“…It has been previously shown that epicardial fat in individuals living with HIV correlates to coronary calcium score [40], plaque prevalence [25] and to an increased risk of adverse cardiovascular events [23]. Using CCTA, Brener et al [25] and Srinivasa et al [34] showed that epicardial fat volume is associated to noncalcified coronary plaques in HIV patients. Our study adds to the current knowledge by demonstrating an independent relationship between epicardial fat volume and noncalcified plaque volume.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies may be attributed to differences in sex, duration of the infection and ART therapy, as well as CV risk profile. Thus, women with and without HIV had similar volumes of EAT in a study conducted by Srinivasa et al [33], underlining gender‐specific differences in ectopic fat deposition in HIV. However, when groups were stratified by HIV serostatus and high/low EAT, highest levels of immune activation/arterial inflammation markers were observed among HIV‐infected women with excess EAT.…”
Section: Epicardial/pericardial Adipose Tissue (Table 2)mentioning
confidence: 53%
“…Finally, a significant relationship between EAT/PAT volume/density and insulin resistance, as well as a linear relation of EAT/PAT volume with VAT and mixed form lipodystrophy phenotypes have been demonstrated in both HIV men and women in several studies [27,30‐33,36,45,46].…”
Section: Epicardial/pericardial Adipose Tissue (Table 2)mentioning
confidence: 99%
“…The effect of EAT in PLWHIV may differ between sex. Srinivasa et al assessed 55 HIV-positive and 27 HIV-negative women for the impact on EAT on CVD (81). Whilst both groups exhibited a similar EAT volume in the HIV-negative group the EAT volume was significantly associated with CVD risk scores (p=0.02).…”
Section: Beyond Its Regulation Of Myocardial Energy Eat Has Several Other Cardioprotective Functionsmentioning
confidence: 99%